2011
DOI: 10.1158/1940-6207.capr-10-0375
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Is a Potent Inhibitor of Skin Tumor Promotion by 12-O-Tetradecanoylphorbol-13-Acetate

Abstract: Aberrant activation of PI3K/Akt signaling has been implicated in the development and progression of multiple human cancers. During the process of skin tumor promotion induced by treatment with the phorbol ester TPA, activation of epidermal Akt occurs as well as several downstream effectors of Akt, including the activation of mTORC1. Rapamycin, an established mTORC1 inhibitor, was used to further explore the role of mTORC1 signaling in epithelial carcinogenesis, specifically during the tumor promotion stage. Ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 35 publications
10
78
2
Order By: Relevance
“…BK5.PRAS40 T246A mice were significantly less sensitive to TPA-induced epidermal hyperproliferation measured by labeling index (LI) and epidermal thickness (Figures 3a, 3b; p <0.0001, Mann-Whitney U test). These data together with the data in Figure 2 indicate that overexpression of PRAS40 T246A in basal keratinocytes effectively blocked TPA-induced epidermal hyperproliferation, which reproduces the effect of rapamycin observed in our previous studies (Checkley, Rho, 2011, Rho, Kiguchi, 2013). …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…BK5.PRAS40 T246A mice were significantly less sensitive to TPA-induced epidermal hyperproliferation measured by labeling index (LI) and epidermal thickness (Figures 3a, 3b; p <0.0001, Mann-Whitney U test). These data together with the data in Figure 2 indicate that overexpression of PRAS40 T246A in basal keratinocytes effectively blocked TPA-induced epidermal hyperproliferation, which reproduces the effect of rapamycin observed in our previous studies (Checkley, Rho, 2011, Rho, Kiguchi, 2013). …”
Section: Resultssupporting
confidence: 90%
“…As shown in supplemental Figure S1b and S1c, reduction of TPA-induced mTORC1 activation in BK5.PRAS40 T246A mice produced a inhibitory effect similar to that observed with 5 nmol of rapamycin treatment. This dose of rapamycin was previously shown to produce an ~ 50% inhibition in skin tumor promotion by TPA in wild-type mice (Checkley et al , 2011)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from our laboratory demonstrated a strong local anti-inflammatory effect of low dose RAPA when given topically to mice during the process of skin tumor promotion (37). Furthermore, other studies have shown anti-inflammatory effects of RAPA (36), and more recently anti-inflammatory effects of MET (38, 39).…”
Section: Discussionmentioning
confidence: 94%
“…117 Rapamycin also prevents skin tumors induced by phorbol esters. 118 It was assumed that rapalogs delay cancer by targeting cancer cells directly. Yet, there were some indications that the effect might be indirect via targeting normal cells.…”
Section: Mtor In Cancermentioning
confidence: 99%